Continuing Professional Development of Compulsory Secondary Teachers: an Opportunity to Fill the Gaps in Initial Training when Confronted with the Social Problems of Secondary School Students in Andalusia (Spain) - Velasco, Elisa; Venegas, Mar; Sánchez-Miranda, Kiko (Journal of Education Culture and Society, 2025)
Aim. This paper analyses the curriculum relating to continuing professional development of teachers in Andalusia, Southern Spain, focusing on what we define as ‘the social problems of secondary school students’. This training is offered to secondary school teachers by the Andalusian educational system. We understand the term ‘continuing teacher professional development’ as the training given to secondary school teachers during the course of their professional teaching career. This includes all the training activities involved in the preparation of teachers for scientific, technical, didactic and professional areas throughout their working life. Methods. An exhaustive analysis of the 32 Teacher Centres within the Andalusian public education system was carried out. The Teacher Centres are the bodies responsible for providing continuing professional development on broad and diverse subjects to practising teachers during their professional careers. This research was undertaken during the 2018/202 academic year. The data collection followed the technique of documentary analysis of secondary sources, in this case the websites of the 32 Andalusian Teacher Centres. Results. Only 96 of the 1,142 activities training for teachers are used to work on specific structural and generational social problems of secondary school students in Andalusia. Conclusion. The results of this research show that the content of the training is insufficient to address and work on the social problems of Andalusian students.